Strategic Alignment of Technological Innovation for Sustainable Development: Efficiency Evaluation and Spatial Analysis in China’s Advanced Manufacturing Industry - Zhenghan Chen; Quan Zhang; Tianzhen Tang; Mingran Deng (Systems)
Technological innovation is essential to promoting sustainable development in emerging economies as it drives regional coordination and industry upgrading. In order to address the understudied connection between regional coordination and industrial structural transformation, this study examines the spatial dynamics of technological innovation efficiency (TIE) in China’s advanced manufacturing industry (AMI) along the Yangtze River Economic Belt (YREB) from 2007 to 2022. Through a Data Envelopment Analysis (DEA) and Spatial Durbin Model (SDM), we systematically evaluated TIE patterns using panel data from 11 provinces. Our empirical analysis reveals three key findings. (1) The temporal distribution of TIE in AMI in the YREB showed an annual increasing trend. The spatial distribution characteristics showed a gradient distribution disparity between the eastern, central, and western regions, but the regional gap of TIE in AMI is gradually closing. (2) Through the examination of Moran’s I, the spatial spillover effect of TIE in AMI was observed, that is, the TIE is spreading from high-performance provinces to other regions, suggesting that interregional collaboration and knowledge exchange may be beneficial. (3) According to the factor identification study, the main factors affecting the spatial distribution of TIE in AMI are industrialization, human capital, and innovation capability. Interestingly, the effects of information technology and economic progress are not statistically significant, suggesting that cautious government actions are required. By optimizing technological innovation processes and spatial arrangements, this study adds to the expanding body of knowledge on the spatial aspects of technological innovation and provides valuable insights for policymakers looking to enhance global competitiveness and foster sustainable economic growth in the AMI. The findings advance our knowledge of how to support sustainable economic development in emerging nations by highlighting the critical role that innovation and technology management play in removing regional development obstacles and encouraging the modernization of industrial structures.